Cultural Contributors to Smoking Susceptibility Outcomes Among Latino Youth: The Padres Informados/Jovenes Preparados Participatory Trial. Issue 2 (April 2017) - Allen, Michele L.; Hurtado, G. Ali; Garcia-Huidobro, Diego; Davey, Cynthia; Forster, Jean; Reynoso, Ursula; Alvarez de Davila, Silvia; Linares, Roxana; Gonzales, Nancy; Veronica Svetaz, María
Abstract : Padres Informados/Jovenes Preparados is a community-based participatory, family-focused tobacco prevention intervention for immigrant Latino families of adolescents. We conducted a participatory randomized controlled trial including 352 Latino families. Parents and youth in the intervention condition engaged in eight family skill building sessions. Participants completed baseline and 6-month postintervention surveys assessing smoking susceptibility and contextual factors. While the intervention did not affect smoking susceptibility overall, it resulted in lower smoking susceptibility among youth in families with less adherence to traditional Latino cultural values. This family cultural orientation is a key consideration for tobacco prevention interventions focused on Latino youth.